Former British Cycling and Team Sky doctor ordered testosterone to improve performance, tribunal finds - Dyer, C. (British Medical Journal, 2021)
The former chief doctor for British Cycling and Team Sky, Richard Freeman, ordered banned testosterone "knowing or believing it was to be administered to an athlete to improve their athletic performance," a medical practitioners tribunal has concluded.